Critical reviews of Load flow methods for well, ill and unsolvable condition - Shahriari, A.; Mokhlis, Hazlie; Bakar, A.H.A. (Journal of Electrical Engineering-Elektrotechnicky Casopis, 2012)
This paper presents a critical review of Load flow methods in well, ill and unsolvable conditioned systems. The comparison studies deals with multiple load flow solution (MLFS), second-order load-flow (SOLF) and continuation load flow (CLF). The ability of theses method to return from unsolvable solution to a solvable solution in load flow analysis is analyzed and discuss thoroughly. Special attention is given to the problems and techniques to provide optimal recommendations of the parameters that are used in these load flow methods. A part of the reviews, this paper also presents the comparison of numerical result using different type of aforesaid load flow methods for well and ill-conditioned systems.